The elegance of the hedgehog - Barbery, Muriel, 1969- (Europa Editions, 2008)
The lives of fifty-four-year-old concierge Rene Michel and extremely bright, suicidal twelve-year-old Paloma Josse are transformed by the arrival of a new tenant, Kakuro Ozu.